In situ XPS investigations of Cu1-xNixZnAl-mixed metal oxide catalysts used in the oxidative steam reforming of bio-ethanol - Velu, S.; Suzuki, K.; Vijayaraj, M.; Barman, S.; Gopinath, Chinnakonda S. (Applied Catalysis B - Environmental, 2005)
A series of CuNiZnAl-multicomponent mixed metal oxide catalysts with various Cu/Ni ratios were prepared by the thermal decomposition of Cu1-xNixZnAl-hydrotalcite-like precursors and tested for oxidative steam reforming of bio-ethanol. Dehydrogenation of EtOH to CH3CHO is favored by Cu-rich catalyst. Introduction of Ni leads to C-C bond rupture and producing CO, CO2 and CH4. H-2 yield (selectivity) varied between 2.6-3.0 mol/mol of ethanol converted (50-55%) for all catalysts at 300 degreesC. The above catalysts were subjected to in situ XPS studies to understand the nature of active species involved in the catalytic reaction. Core level and valence band XPS as well as Auger electron spectroscopy revealed the existence of Cu2+, Ni2+ and Zn2+ ions on calcined materials. Upon in situ reduction at reactions temperatures, the Cu2+ was fully reduced to Cu-0. while Ni2+ and Zn2+ were partially reduced to Ni-0 and Zn-0, respectively. On reduction, the nature of ZnO on Cu-rich catalyst changes from crystalline to amorphous, relatively inert and highly stabilized electronically. Relative concentration of the Ni-0 and Zn-0 increases upon reduction with decreasing Cu-content. Valence band results demonstrated that the overlap between 3d bands of Cu and Ni was marginal on calcined materials, and no overlap due to metallic clusters formation after reduction. Nonetheless, the density of states at Fermi level increases dramatically for Ni-rich catalysts and likely this influences the product selectivity. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: auger electron spectroscopy; Autothermal reforming; Bio-ethanol; copper oxide; fuel cell; Hydrogen; hydrotalcite; mixed metal oxides; nickel oxide; oxidative steam reforming; Steam reforming; XPS

Heteropolyacid supported on montmorillonite catalyst for dehydration of dilute bio-ethanol - Bokade, Vijay V.; Yadav, Ganapati D. (Applied Clay Science, 2011)
Vapour phase dehydration of dilute bio-ethanol (EtOH) to ethylene (E) and diethyl ether (DEE) is industrially relevant. Ethylene is an important raw material for many petrochemical products and Diethyl ether (DEE) can be used as an alternative fuel. The efficacy of montmorillonite (K-10) and dodecatungestophosphoric acid (DTPA) supported on montmorillonite (DTPA/K-10), has been evaluated in the current work in the dehydration of dilute bio-ethanol (80%m/m). The dehydration of ethanol and cracking of diethyl ether were studied independently. 30% m/m DTPA/K-10 was found to be more active with 74% ethanol conversion and 92% ethylene selectivity at 250 degrees C in comparison with other acid catalysts used. The merit of the process lies in its use of dilute bio-ethanol, a new avenue for ethylene production from a non-petroleum feedstock. Kinetic interpretation has been made by studying the important process parameters by using 30%m/m DTPA/montmorillonite as the catalyst. The mechanism of the dehydration of ethanol reaction suggests that two types of sites are responsible. The dehydration of ethanol and cracking of diethyl ether are second order reactions with weak adsorption of species. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bio-ethanol; dehydration; Diethyl ether; Ethylene; Heteropolyacid